Angular momentum and arboreal stability in common marmosets (Callithrixjacchus). Issue 4 (19th December 2014) - Chadwell, Brad A.; Young, Jesse W.; Lewton, Kristi; Nalley, Thierra K.
ABSTRACT Despite the importance that concepts of arboreal stability have in theories of primate locomotor evolution, we currently lack measures of balance performance during primate locomotion. We provide the first quantitative data on locomotor stability in an arboreal primate, the common marmoset (Callithrix jacchus), predicting that primates should maximize arboreal stability by minimizing side‐to‐side angular momentum about the support (i.e., Lsup). If net Lsup becomes excessive, the animal will be unable to arrest its angular movement and will fall. Using a novel, highly integrative experimental procedure we directly measured whole‐body Lsup in two adult marmosets moving along narrow (2.5 cm diameter) and broad (5 cm diameter) poles. Marmosets showed a strong preference for asymmetrical gaits (e.g., gallops and bounds) over symmetrical gaits (e.g., walks and runs), with asymmetrical gaits representing >90% of all strides. Movement on the narrow support was associated with an increase in more "grounded" gaits (i.e., lacking an aerial phase) and a more even distribution of torque production between the fore‐ and hind limbs. These adjustments in gait dynamics significantly reduced net Lsup on the narrow support relative to the broad support. Despite their lack of a well‐developed grasping apparatus, marmosets proved adept at producing muscular "grasping" torques about the support, particularly with the hind limbs. We contend that asymmetrical gaits permit small‐bodied arboreal mammals, including primates, to expand "effective grasp" by gripping the substrate between left and right limbs of a girdle. This model of arboreal stability may hold important implications for understanding primate locomotor evolution. Am J Phys Anthropol 156:565–576, 2015. © 2014 Wiley Periodicals, Inc.